Housing wealth and household consumption in urban China. (June 2020) - He, Zekai; Ye, Jingjing; Shi, Xiuzhen
Using a large Chinese household survey data set, we investigate the effect of home value appreciation on urban household consumption. The paper identifies the causal effect of housing wealth using both Two-Stage Least Squares (2SLS) estimates and regression discontinuity designs. The research demonstrates that the housing boom in China has resulted in higher consumption and that a 10% increase in home wealth raises overall consumption by approximately 3%. The average marginal propensity to consume out of housing wealth is about 5 cents with substantial heterogeneity across household characteristics. The findings highlight the role of mortgage debts, health insurance, education and risk preference in explaining the variation in household consumption. Our results persist when we adopt different proxies for housing wealth.